Pengaruh Konsentrasi Silika Dan Beda Tekanan Statis Uap Terhadap Kecepatan Scaling Pada Model Pipa Panas Bumi = Effect of Silica Concentrations and Steam Static - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT Scaling or deposition on the geothermal transmission pipes wall happens if the working steam which flows in it contains some minerals, like Silica and Carbonate. This research used steam as a model for geothermal fluid. The steam as fluid was generated by a boiler. Three solutions of silica were used, those were 57,1, 71,7, and 93,5 ppm. These concentrations were based on the solubility of quartz at 133,5Â°C, and a working pressure of 2 atg, and three static pressure differences of 0,4, 1,0 and 1,5 atg. The steam at certain condition flowed in the specimen for six hours. The scale thickness on the specimen wall was measured and compared to the copper wire of 120 grn diameter. The deposition rates, which depend on the surface roughness, static pressure differences , and silica concentration in the solution, could be approached by linear equations.